Internet Connection Obstacles in General Speaking Courses and Their Influence on Learning Effectiveness - Hasanatul Fitri; Didik Himmawan; Hana Wulandari; Indah Ardianti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Indonesia in 2020 was hit by a covid-19 pandemic, all activities were carried out online because it was to prevent and reduce the spread of the covid-19 virus. In learning activities, it also uses an online system at the school and university levels. An internet connection, and supporting devices such as laptops or gadgets are important in online learning. The obstacles experienced by students in general are inadequate internet connections, or constrained due to weather. Therefore, this study aims to analyze the difficulties of students in learning speaking courses with the constraints of internet conditions and their effect on the effectiveness of learning. This research uses qualitative methods and the research design is a case study. The results of this study can be concluded that internal factors such as network constraints or internet connections faced by students in the general speaking learning process are quite influencing the learning process, especially for students whose residences do not have a good internet network. However, online learning also has a positive side, namely that students can study anywhere even if they are outside the home, they can still participate in learning activities.